Association of METS-IR index with prevalence of gallbladder stones and the age at the first gallbladder stone surgery in US adults: A cross-sectional study - Wang, Jin; Yang, Junping; Chen, Yan; Rui, Jing; Xu, Maoqi; Chen, Mingwei (Frontiers in Endocrinology, 2022)
Objective：The purpose of this study was to assess the correlation between the METS-IR index and gallbladder stoneprevalence in US adults, as well as the age at first gallbladder stone surgery. Methods：A logistic regression analysis, subgroup analysis, and dose-response curve were computed for participants in the 2017-2018 National Health and Nutrition Examination Survey (NHANES) to assess the relationship between the METS-IR index and gallbladder stone prevalence and age at first surgery for gallbladder stones. Results：This study ultimately included 9452 participants aged >20 years, of whom 534 self-reported a history of gallbladder stones, and after adjusting for all confounders, each unit increase in METS-IR index was associated with a 3.3% increase in gallbladder stone prevalence (OR= 1.033, 95% CI: 1.0258, 1.0403) along with an earlier age at first gallbladder stone surgery 0.26 years (β= -0.26, 95% CI: -0.35, -0.17), stratified analysis showed that increased METS-IR index was associated with increased prevalence of gallbladder stones in all subgroups, and the dose-response curve showed a positive linear correlation between METS-IR index and prevalence of gallbladder stones, while a negative linear correlation was observed between increased METS-IR index and age at first gallbladder stone There was a negative linear correlation between age at surgery. Conclusion: The METS-IR index has been positively associated with gallbladder stone prevalence, thereby contributing to age at first surgery for gallbladder stones. However, the causal relationship between the METS-IR and gallbladder stones cannot be concluded.